A pleiotropic variant in DNAJB4 is associated with multiple myeloma risk. Issue 2 (1st October 2022) - Dicanio, Marco; Giaccherini, Matteo; Clay‐Gilmour, Alyssa; Macauda, Angelica; Sainz, Juan; Machiela, Mitchell J.; Rybicka‐Ramos, Malwina; Norman, Aaron D.; Tyczyńska, Agata; Chanock, Stephen J.; Barington, Torben; Kumar, Shaji K.; et al.
Abstract: Pleiotropy, which consists of a single gene or allelic variant affecting multiple unrelated traits, is common across cancers, with evidence for genome‐wide significant loci shared across cancer and noncancer traits. This feature is particularly relevant in multiple myeloma (MM) because several susceptibility loci that have been identified to date are pleiotropic. Therefore, the aim of this study was to identify novel pleiotropic variants involved in MM risk using 28 684 independent single nucleotide polymorphisms (SNPs) from GWAS Catalog that reached a significant association ( P < 5 × 10 −8 ) with their respective trait. The selected SNPs were analyzed in 2434 MM cases and 3446 controls from the International Lymphoma Epidemiology Consortium (InterLymph). The 10 SNPs showing the strongest associations with MM risk in InterLymph were selected for replication in an independent set of 1955 MM cases and 1549 controls from the International Multiple Myeloma rESEarch (IMMEnSE) consortium and 418 MM cases and 147 282 controls from the FinnGen project. The combined analysis of the three studies identified an association between DNAJB4 ‐rs34517439‐A and an increased risk of developing MM (OR = 1.22, 95%CI 1.13‐1.32, P = 4.81 × 10 −7 ). rs34517439‐A is associated with a modified expression of the FUBP1 gene, which encodes a multifunctional DNA and RNA‐binding protein that it was observed to influence the regulation of various genes involved in cell cycle regulation, among which various oncogenes and oncosuppressors. In conclusion, with a pleiotropic scan approach we identified DNAJB4 ‐rs34517439 as a potentially novel MM risk locus. Abstract : What's new? Genetic variants can have multiple, seemingly unrelated, effects. Often, these so‐called "pleiotropic" variants play a role in cancer. Here, the authors set out to identify new pleiotropic variants involved in multiple myeloma (MM) risk. They analyzed 28, 684 independent single nucleotide polymorphisms (SNPs) that had been identified in genome‐wide association studies as having an effect on a human trait. This analysis revealed an association between increased MM risk and a variant called DNAJB4 ‐rs34517439‐A. That variant has been associated with changes in expression of a DNA‐ and RNA‐binding protein that helps regulate cell cycle genes.